2010
DOI: 10.1002/mds.22732
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline 1‐year therapy in multiple‐system‐atrophy: Effect on clinical symptoms and [11C] (R)‐PK11195 PET (MEMSA‐trial)

Abstract: The aim of the study was to investigate the efficacy of the antibiotic minocycline as a drug treatment in patients with Multiple-System-Atrophy Parkinson-type (MSA-P). Sixty-three patients were randomized to minocycline 200 mg/d (n = 32) or a matching placebo (n = 31). The primary outcome variable was the change in the value of the motor score of the Unified Multiple-System-Atrophy Rating-Scale (UMSARSII) from baseline to 48 weeks. Secondary outcome variables included subscores and individual Parkinsonian symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(126 citation statements)
references
References 39 publications
6
117
1
2
Order By: Relevance
“…Double-blind randomized clinical trials examining the efficacy of minocycline in a variety of neurodegenerative disease, including Parkinson disease 48, 49 , Amyotropic lateral sclerosis (ALS) 50, 51 , and Huntington’s Disease 52, 53 have not demonstrated definitive efficacy in attenuating disease progression. In these clinical trials, the precise target of minocycline’s mechanism of action was not identified, and therefore target engagement was not confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Double-blind randomized clinical trials examining the efficacy of minocycline in a variety of neurodegenerative disease, including Parkinson disease 48, 49 , Amyotropic lateral sclerosis (ALS) 50, 51 , and Huntington’s Disease 52, 53 have not demonstrated definitive efficacy in attenuating disease progression. In these clinical trials, the precise target of minocycline’s mechanism of action was not identified, and therefore target engagement was not confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…This provisional scale which includes these eight items might have with the potential to sensitively detect changes in MSA symptoms that occur over a short period. Clinical trials for MSA, such as those that examined the effects of minocycline [39] and rifampicin [40], have not yet yielded an effective treatment for MSA. This may have been due to inadequate sample size, study design, and outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Différentes molécules ont été étudiées ces dernières années dans l'AMS avec des résultats décevants, comme la rasagiline, l'hormone de croissance, le riluzole, la minocycline ou encore la rifampicine [34][35][36][37][38].…”
Section: Les Essais Thérapeutiquesunclassified